Regulation of Electron Transport in Plant Mitochondria under State 4 Conditions - Moore, Anthony L. (1991)
The regulation of electron transport in pea (Pisum sativum L.) leaf mitochondria under state 4 conditions has been investigated by simultaneously monitoring oxygen uptake, the steady-state reduction level of ubiquinone, and membrane potential. Membrane potentials were measured using a methyltriphenylphosphonium electrode while a voltametric technique was used to monitor changes in the steady-state reduction levels of quinone. It was found that the addition of glycine to mitochondria oxidising malate in state 4 led to a marked increase in the rate of O(2) uptake and increased both the membrane potential and reduction level of the quinone pool. Increases in the state 4 respiratory rate were attributed to both an increase in driving flux, due to increased Q-pool reduction, and in membrane potential. Due to the nonohmic behavior of the inner membrane, under these conditions, an increase in potential would result in a considerable rise in proton conductance. Measurement of dual substrate oxidation, in the presence of n-propylgallate, revealed that the increase in respiratory activity was not mediated by the alternative oxidase. Similar increases in membrane potential and the level of Q-pool reduction were observed even in the presence of rotenone suggesting that the rotenone-insensitive pathway is a constitutive feature of plant mitochondria and may play a role in facilitating rapid state 4 rates even in the presence of a high energy charge.